Inovasi Virtual Reality dalam Pendampingan Manasik Haji Plus KBIHU As Sa’diyah Kecamatan Senori KabupatenTuban - Muhammad Abdul Mujib; Moh. Dhofir Jenny Al Fahmi (Journal of Innovation and Contribution to Community Service, 2025)
This study aims to examine the effectiveness of the Hajj Ritual Assistance Plus program implemented by KBIHU As-Sa’diyah, Senori District, Tuban Regency, in improving the readiness of prospective pilgrims through innovative guidance methods. The research employs a qualitative case study approach to investigate the application and impact of the program in a real-world and contextual setting. Data were collected through in-depth interviews with KBIHU organizers, pilgrims, and related stakeholders, as well as direct observation of manasik hajj (ritual rehearsal) activities and the use of digital tools. The program incorporates experiential learning, digital-based materials (video tutorials and e-books), as well as online and offline consultation, aiming to build pilgrims’ mental, physical, and spiritual preparedness. The findings show that the program significantly improves pilgrims' understanding of hajj rituals, physical readiness, and spiritual awareness. Despite challenges such as limited access to digital tools for elderly participants and infrastructure constraints, the program presents a promising model for hajj preparation that could be adopted by other KBIHUs in Indonesia